The political economy of illegal drugs in the Andes - Thoumi, Francisco (2016)
This article puts forward some ideas on illegal drugs in the Andes from a supply and demand perspective. The author explores why some countries produce illegal drugs and others do not, disregarding conventional perceptions that locate poverty, inequality, economical crises and corruption as the main explanations for the me of drug trafficking activities. Toumi argues that while such factors may contribute to drug trafficking they are not its causes. Finally, by locating the problem in social and institutional factors, the author makes clear that solutions require structural changes in society.